Pengaruh Brand Awareness Terhadap Purchase Decision Shopeefood Melalui Trust Pada Generasi Z Di Kota Denpasar - Kadek Bayu Mediana; Ni Putu Yuliana Ria Sawitri; Cokorda Istri Agung Vera Nindia Putri (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
The importance of understanding the factors that influence a purchasing decision, especially among Generation Z who are the dominant users. In Denpasar City as one of the growth centers in Bali, the trend of digital service users is increasing, Denpasar is a potential market for digital platforms including food delivery services. This research uses a quantitative approach with a survey method through distributing questionnaires to 150 respondents who are active ShopeeFood users aged 17-27 years in Denpasar City. The purpose of this study was to determine the effect of each variable, namely Brand Awareness on Trust, Trust on Purchase Decision, Brand Awareness on Purchase Decision, and Trust which plays a role in mediating between the influence of Brand Awareness on ShopeeFood Purchase Decision on generation Z in Denpasar City. The results found in this study are that Brand Awareness has a positive and significant effect on ShopeeFood Trust in generation Z in Denpasar City, Trust has a positive and significant effect on ShopeeFood Purchase Decision in generation Z in Denpasar City, Brand Awareness has a positive and significant effect on ShopeeFood Purchase Decision in generation Z in Denpasar City, and Trust plays a role in mediating the effect of Brand Awareness on Purchase Decision